2014
DOI: 10.1016/j.ecolmodel.2014.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effectiveness of green infrastructures on urban flooding reduction: A community scale study

Abstract: a b s t r a c tThe risk of urban flooding is increasing as a result of rapid urbanization. Green infrastructure (GI) is an emerging planning and design concept to mitigate urban flooding. A community scale simulation model was developed to quantify the effectiveness of GI on reducing the volume and peak flow of urban flooding. Five scenarios, namely expanding green space, converting to concave green space, constructing a runoff retention structure, converting to porous brick pavement, and combining previous fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(130 citation statements)
references
References 22 publications
6
123
0
1
Order By: Relevance
“…This result is similar to one where it was found that creating green spaces such as street plantings in a concave rather than in a convex form by raising the elevation higher than surrounding roadways can be advantageous for reducing flooding by rainwater infiltration. In the case of reconstructing all green spaces in a community to a depth of 5 cm, it was found that runoff could be reduced by a maximum of 16% and the peak outflow by about 25% [5]. Concave-shaped green spaces could be interpreted in the same context as Type 3 green spaces.…”
Section: Discussionmentioning
confidence: 90%
“…This result is similar to one where it was found that creating green spaces such as street plantings in a concave rather than in a convex form by raising the elevation higher than surrounding roadways can be advantageous for reducing flooding by rainwater infiltration. In the case of reconstructing all green spaces in a community to a depth of 5 cm, it was found that runoff could be reduced by a maximum of 16% and the peak outflow by about 25% [5]. Concave-shaped green spaces could be interpreted in the same context as Type 3 green spaces.…”
Section: Discussionmentioning
confidence: 90%
“…Impacts of green infrastructures on stormwater infiltration, retention and storage capacity are accounted for in calculating runoff. Detail information on the model can be found in Liu et al (2014).…”
Section: Model Descriptionmentioning
confidence: 99%
“…Many researches have studied the hydrological performance of green infrastructure practices on a laboratory, a pilot scale and insitu full scale (Abbott and Comino-Mateos, 2003;Alfredo et al, 2010;Chapman and Horner, 2010;Dietz, 2007;Fassman and Blackbourn, 2010;Qin et al, 2013). Although the green infrastructure performance on reducing runoff volumes has been extensively investigated, few studies have attempted to compare the reduction effectiveness between integrated green infrastructure and single facilities (Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…GI plays an important role in the field of flood risk management in urban areas, and its potential for flood risk reduction has been demonstrated in numerous studies. For instance, Liu et al [32] have investigated the impact of GI on a typical neighborhood in Beijing and have found that by implementing integrated GI, runoff of a five-year return period storm has been 100% reduced. In Augustenborg and Malmo in Sweden, GI has reduced stormwater runoff by 50% [33].…”
Section: The Rise Of Green Infrastructurementioning
confidence: 99%